Developing Nationalism Awareness through Literature Learning of Indonesian National Songs via Mobile Assisted Language Learning (MALL): A Quantitative Pre-Test and Post-Test Study - Wuntu, Ceisy Nita; Ali, Muhammad Ilham; Mamentu, Agustine Clara (MARAS : Jurnal Penelitian Multidisiplin, 2025)
This study aims to develop and strengthen students’ nationalistic awareness through a literature learning model that integrates Indonesian national songs—Indonesia Pusaka, Syukur, Gugur Bunga, and Sepasang Mata Bola—using Mobile Assisted Language Learning (MALL). The focus is on embedding values of patriotism and love of the nation while enhancing language learning in a digital learning environment. The research employs a quantitative design with a simple experimental approach. Data were collected through pre-test and post-test to measure students’ level of nationalistic understanding and language comprehension before and after the implementation of the model. The participants consisted of undergraduate students in an English education program who were introduced to the lyrical and cultural dimensions of the songs via mobile learning applications. Findings indicate a significant improvement in students’ comprehension and appreciation of the patriotic values embedded in the selected songs. The post-test results demonstrated higher scores compared to the pre-test, showing that students not only acquired better linguistic understanding but also developed a deeper sense of national pride and identity. The use of MALL provided flexibility, accessibility, and interactive engagement, making literature learning more effective and appealing to digital-native students.